PEMETAAN BENTUK DAN PENCEGAHAN PENIPUAN E-COMMERCE - Arista Dewi, Ni Komang; Mahyuni, Luh Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.09.TAHUN 2020, 2020)
The rapid growth of buying and selling transactions, makes electronic fraud also increased so that many consumers have suffered losses due to fraud occurred . The purpose of this research is to find out the types of fraud that can occur in e-commerce and the prevention that can be done. The author presents a review with an interpretive approach to the related articles, through mapping on articles collected from Google Scholar, Elsevier, Springer, Taylor & Francis, and MDPI ( Multidisciplinary Digital Publishing Institute ) . From these sources, the author collected 105 articles, after articles selection process based on the last 10 years and the suitability of the discussion finally the author collected 55 articles. The results of this research is the authors found various types of fraud in four categories of e-commerce, fraud in the payment system , and fraud in e-commerce involving customers. Modern methods of fraud detection are also presented in this research, such as data mining, Bayesan networks, algorithms, vector support machine, genetic programming, tress decision making, Adaptive Neuro-Fuzzy Inference Systems, Protection Assistance Websites (PAW), and Models Privacy Antecedent-Privacy Concern-Outcomes (APCO). With the explanation on the results, consumers are expected to be more careful when making transactions on e-commerce to avoid fraud.